Development and characterizations of novel aqueous-based LSCF suspensions for inkjet printing. Issue 11 (1st August 2018) - Chen, Zhangwei; Ouyang, Jing; Liang, Wenlang; Yan, Zhi-chao; Stadler, Florian; Lao, Changshi
Abstract: Stability often remains challenging when preparing suitable ceramic suspensions for inkjet printing use. In this study, we report the development and characterizations of a novel aqueous-based SOFC cathode suspension with superb dispersivity. Two dispersants TEA and PAA were used for comparison. Suspension formulations were optimized with the aid of zeta potential, viscosity and surface tension measurements, as well as sedimentation, drying and sintering experiments. Results showed that the best dispersivity can be achieved for the as-prepared suspension named INK-T1 at modulated pH of 5.8 (zeta potential of 41.8 mV) using TEA as dispersant. Desirable printability was also demonstrated by inkjet printing tests. The long term stability and homogeneity with a shelf time > 90 days was reached, against the poor performance, i.e. fast sedimentation, of other suspensions outside the optimal pH range. SEM results further assured INK-T1's excellent quality that can be used to prepare defect-free LSCF layers. Highlights: Aqueous-based LSCF suspensions having properties within the inkjet printing range were obtained. Dispersant TEA was used to modulate the ink viscosity and surface tension. Different ink rheological behaviors were measured and analyzed. A proper suspension stability (zeta potential) was achieved by using TEA dispersant. Stability over a prolonged time (> 90 days) was achieved.